Anti-skid coating material with wet self-adhesion function and preparation method of anti-skid coating material

By using a composite material of polydopamine/sodium polyacrylate micro powder and PVB binder, the problem of reduced friction coefficient of anti-slip coatings in wet environments is solved, achieving high-efficiency anti-slip performance and safety of floor mats, while meeting environmental protection requirements.

CN121699455APending Publication Date: 2026-03-20ZHENGZHOU MEIJIN HOME FURNISHING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610016223.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-01-07
Publication Date
2026-03-20

AI Technical Summary

Technical Problem

Existing anti-slip coatings have a lower coefficient of friction in wet environments, causing the floor mats to slide and shift, increasing the risk of falls. Furthermore, the dopamine coating wears down under long-term friction or cleaning conditions, affecting its anti-slip effect.

Method used

The composite material of polydopamine/sodium polyacrylate micro powder and PVB binder is used. By generating polydopamine in an alkaline environment, a non-slip coating with wet self-adhesive function is formed, which enhances the friction of the ground and absorbs moisture, thereby improving the anti-slip ability of the floor mat.

Benefits of technology

It significantly improves the coefficient of friction of floor mats under wet and slippery conditions, reduces the risk of slipping, and enhances the safety and comfort of the indoor environment, while the materials are environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121699455A_ABST
    Figure CN121699455A_ABST
Patent Text Reader

Abstract

The invention particularly relates to an anti-skid coating material with a wet self-adhesion function and a preparation method thereof, and the method comprises the following steps: adding a sodium polyacrylate aqueous solution into a dopamine hydrochloride aqueous solution, uniformly mixing, then adding a buffer solution to adjust the pH value to be alkaline, standing for reaction, filtering, washing, and drying to obtain the anti-skid coating material with the wet self-adhesion function. A mixed solution containing sodium polyacrylate / polydopamine is obtained; drying, crushing and ball-milling the obtained mixed solution to obtain sodium polyacrylate / polydopamine micro powder; adding PVB into absolute ethyl alcohol, dissolving to obtain a PVB ethanol solution, then adding the obtained sodium polyacrylate / polydopamine micro powder into the PVB ethanol solution, homogenizing at a high speed to obtain a mixed liquid, and carrying out vacuum defoaming to obtain the anti-skid coating material which takes PVB as a binder and has a wet self-adhesion function. When the obtained coating material is coated on an object, the micro powder is bonded on a base body to form a rough surface, so that the friction force of the ground can be effectively increased, the dry and wet friction coefficient is remarkably improved, and people are safer during walking.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of anti-slip coating materials technology, specifically to an anti-slip coating material with wet self-adhesion function and its preparation method. Background Technology

[0002] In daily life, floor mats are often laid on the ground to prevent moisture, remove mud and dust, and keep indoor floors clean. Their bottoms are mostly smooth surfaces with a very low coefficient of friction, especially when the ground is damp. When a person steps on a floor mat, it may slip and shift, causing instability and a fall. Cases collected by the National Injury Surveillance System show that in 2022, my country monitored a total of 261,000 fall / drop cases, accounting for approximately 37% of all injury cases, ranking first among accidental injuries. Of these, 54% of cases occurred at home or in public residential areas. Based on this, it can be inferred that falls / drops in these locations are primarily caused by physical falls.

[0003] In homes and public residences, flooring materials are mainly wood flooring and ceramic tiles. Areas requiring enhanced slip resistance are typically damp environments such as around bathrooms. These environments are relatively small, and the most common anti-slip measure is adding anti-slip mats. Among various anti-slip treatments, anti-slip coatings are a convenient and effective method, applicable to a wide range of surface conditions. Anti-slip coatings are functional materials that improve the friction of object surfaces, forming a high-friction coefficient anti-slip surface. This increases surface friction, reducing the risk of slips and falls, and preventing property damage. So-called "anti-slip coatings" on the market only provide slip resistance when the surface is dry; they become slippery when wet, and the vast majority of slip accidents occur on wet surfaces.

[0004] In recent years, biomimetic materials research inspired by the adhesive properties of mussels has provided new ideas for anti-slip coatings. Dopamine (DA), a natural catechol, is rich in functional groups such as hydroxyl, amino, and catechol groups on its surface. Under alkaline conditions, it can oxidize and self-polymerize to form polydopamine (PDA). PDA has extremely strong adhesion, can firmly adhere to a variety of organic and inorganic surfaces, and is environmentally friendly, thus attracting much attention in the field of functional coatings. Introducing dopamine into the coating system can not only enhance the compatibility between components but also improve the bonding strength between the coating and the substrate, providing a feasible path for developing high-performance anti-slip coatings. However, PDA coatings may gradually wear down under long-term friction or frequent cleaning conditions, affecting the durability of the anti-slip effect. Although PDA has good surface adhesion and hydrophilicity, the anti-slip performance of coatings relying solely on PDA in immersion or high-humidity environments still needs further optimization. Process control and raw material costs during large-scale application of dopamine may limit its practical application. Therefore, it is essential to develop a polydopamine composite material that meets the above requirements for coatings. Summary of the Invention

[0005] To address the problems existing in the prior art, this invention proposes an anti-slip coating material with wet self-adhesive function and its preparation method. Applying the coating of this invention to floor mats effectively increases the wet friction coefficient, thereby improving the anti-slip capability of the floor mats.

[0006] To achieve the above objectives, the technical solution of the present invention is implemented as follows: A non-slip coating material with wet self-adhesive function and its preparation method, the method comprising the following steps: (1) Add 0.5 to 4 parts of dopamine hydrochloride to 100 parts of deionized water and stir to dissolve the dopamine hydrochloride to obtain an aqueous solution of dopamine hydrochloride. Add 30 to 50 parts of sodium polyacrylate aqueous solution with a mass fraction of 20% to 50% to the aqueous solution of dopamine hydrochloride. After mixing evenly, add tris(hydroxymethyl)aminomethane-hydrochloric acid buffer solution (Tris-HCl buffer solution) to adjust the pH value to 8.0-9.0. Then let it stand at 30 to 50°C for 6 to 12 hours. During this process, due to the alkaline environment provided by the buffer solution, dopamine hydrochloride is polymerized in situ to generate polydopamine, and a mixed solution containing sodium polyacrylate / polydopamine is obtained. (2) The mixed solution of sodium polyacrylate / polydopamine obtained in step (1) is dried at 60-100℃, and then pulverized and ground in a ball mill to obtain water-absorbing sodium polyacrylate / polydopamine micro powder with a diameter of 1-3μm. (3) Add 3-8 parts of PVB to 100 parts of anhydrous ethanol solvent, stir at high speed at room temperature for 3-6 hours until completely dissolved to obtain a PVB solution, add 3-8 parts of sodium polyacrylate / polydopamine micro powder from step (2) to the above solution, and then treat it with a high-speed dispersion homogenizer at a speed of 4000-6000 r / min for 6-15 min to obtain a uniform mixed liquid; after vacuum degassing, a non-slip coating material with wet self-adhesive function using PVB as binder is obtained.

[0007] The application of the anti-slip coating material with wet self-adhesion function in anti-slip floor mats.

[0008] The beneficial effects of this invention are: 1. This method uses polydopamine / sodium polyacrylate micropowder as the absorbent material and PVB as the binder to prepare a coating material. PVB is a polymer with a six-membered ring acetal structure formed by the reaction of the carbonyl group in butyraldehyde with two adjacent hydroxyl groups in polyvinyl alcohol. PVB resin has good flexibility and flexural properties, a low glass transition temperature, and good corrosion resistance, impact resistance, electrical insulation, and film-forming properties. It also has excellent adhesion to materials such as glass, metal, and ceramics, and exhibits strong adhesion when used as a binder component in coatings. In this invention, the secondary hydroxyl groups in the PVB molecular chain can form hydrogen bonds with dopamine and sodium polyacrylate, thereby increasing the compatibility with polydopamine / sodium polyacrylate micropowder. 2. In this invention, when a wet-adhesive self-adhesive anti-slip coating material with PVB as a binder is applied to the surface of an object, the micro-powder is adhered to the substrate, forming a rough surface. This effectively increases the friction of the ground, making walking safer. The wet friction coefficient is significantly improved. Simultaneously, this material or treatment technology can absorb ground moisture, keeping the ground dry, further reducing the risk of slipping and improving indoor comfort. Its application in the field of floor mat coating materials has broad prospects. 3. Introducing sodium polyacrylate, a superabsorbent polymer, into the coating material can significantly increase the coating's water absorption rate. However, superabsorbent polymers are soluble in water, resulting in excessive solubility. This invention first uses polydopamine to crosslink sodium polyacrylate. Polydopamine contains numerous hydroxyl and imino groups, which interact with sodium polyacrylate, forming crosslinks and reducing solubility. Then, after blending polydopamine / sodium polyacrylate micropowder with a PVB solution, the secondary hydroxyl groups in the PVB molecular chain can form hydrogen bonds with both dopamine and sodium polyacrylate, increasing compatibility while reducing sodium polyacrylate solubility, thus improving the coating's mechanical properties and adhesion to the substrate. 4. Polydopamine, due to its structure incorporating key components of adhesive proteins, has been proven to possess superior adhesive properties. Introducing dopamine into absorbent coating materials endows the coating with excellent self-adhesive properties, enabling it to stably adhere to various substrate surfaces. In particular, when polydopamine / sodium polyacrylate comes into contact with a moist substrate, it rapidly absorbs interfacial water to form a hydrogel. Simultaneously, the functional groups on the surface of the polydopamine / sodium polyacrylate hydrogel can bind with the functional groups on the substrate surface through physical interactions, thereby promoting wet adhesion and acting like a suction cup. 5. The sodium polyacrylate, PVB, dopamine hydrochloride, and other additives used in this invention are all environmentally friendly. Therefore, this invention conforms to the national environmental protection concept and meets the requirements of sustainable development. Attached Figure Description

[0009] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0010] Figure 1 Infrared spectra of pure sodium polyacrylate and polydopamine / polyacrylic acid prepared in Example 1.

[0011] Figure 2 The images are scanning electron microscope (SEM) images of the samples. A is the surface of a pure TPE sheet, B is the surface of the floor mat coating prepared in Comparative Example 1, and C is the surface of the floor mat coating prepared in Example 1.

[0012] Figure 3 The image shows the contact angle test results of the floor mat coating prepared in Example 1. Detailed Implementation

[0013] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0014] The raw materials used in the following examples are all commercially available products, including: sodium polyacrylate, Shanghai Maclean Biochemical Technology Co., Ltd.; dopamine hydrochloride, Shanghai Maclean Biochemical Technology Co., Ltd.; polyvinyl butyral (PVB), Shanghai Chenqi Chemical Technology Co., Ltd.; and thermoplastic elastomer (TPE), Dongguan Shanyi Plastics Co., Ltd. Example 1

[0015] This embodiment describes the preparation method of an anti-slip coating material with wet self-adhesive function and a floor mat. The steps are as follows: (1) Add 4 parts of dopamine hydrochloride to 100 parts of deionized water and stir to dissolve the dopamine hydrochloride to obtain an aqueous solution of dopamine hydrochloride. Add 30 parts of sodium polyacrylate aqueous solution with a mass fraction of 50% to the aqueous solution of dopamine hydrochloride. After mixing evenly, add tris(hydroxymethyl)aminomethane-hydrochloric acid buffer solution to adjust the pH value to 8.5. Then let it stand at 50°C for 6 hours. During this process, due to the alkaline environment provided by the buffer solution, dopamine hydrochloride is polymerized in situ to generate polydopamine, and a mixed solution containing sodium polyacrylate / polydopamine is obtained. (2) The mixed solution of sodium polyacrylate / polydopamine obtained in step (1) is dried at 100°C, and then pulverized and ground in a ball mill to obtain water-absorbing sodium polyacrylate / polydopamine micro powder with a diameter of 1-3 μm. (3) Add 3 parts of PVB to 100 parts of anhydrous ethanol solvent and stir at high speed for 3 hours at room temperature until completely dissolved to obtain a PVB solution. Add 8 parts of sodium polyacrylate / polydopamine micro powder to the above solution, and then treat it with a high-speed dispersion homogenizer at a speed of 6000 r / min for 15 min to obtain a uniform mixed liquid. After vacuum degassing, a wet self-adhesive anti-slip coating material with PVB as binder is obtained.

[0016] The coating material prepared above was applied to a self-made thermoplastic elastomer sample (pure TPE was placed in a mold and hot-pressed in a flat vulcanizing bed for 15 minutes at a molding temperature of 170℃ and a pressure of 20MPa). The sample was then dried at 60℃. The resulting floor mat was tested for dry and wet friction coefficients according to standard GB / T 3903.37-2008. The measured dry friction coefficient was 0.62, and the wet friction coefficient was 0.82. Example 2

[0017] This embodiment describes the preparation method of an anti-slip coating material with wet self-adhesive function and a floor mat. The steps are as follows: (1) Add 0.5 parts of dopamine hydrochloride to 100 parts of deionized water and stir to dissolve the dopamine hydrochloride to obtain an aqueous solution of dopamine hydrochloride. Add 50 parts of sodium polyacrylate aqueous solution with a mass fraction of 30% to the aqueous solution of dopamine hydrochloride. After mixing evenly, add tris(hydroxymethyl)aminomethane-hydrochloric acid buffer solution to adjust the pH value to 8.5. Then let it stand at 30°C for 12 hours. During this process, due to the alkaline environment provided by the buffer solution, dopamine hydrochloride is polymerized in situ to generate polydopamine, and a mixed solution containing sodium polyacrylate / polydopamine is obtained. (2) The mixed solution of sodium polyacrylate / polydopamine obtained in step (1) is dried at 60°C, and then pulverized and ground in a ball mill to obtain water-absorbing sodium polyacrylate / polydopamine micro powder with a diameter of 1-3 μm. (3) Add 8 parts of PVB to 100 parts of ethanol solvent and stir at high speed for 3 hours at room temperature until completely dissolved to obtain a PVB solution. Add 3 parts of sodium polyacrylate / polydopamine micro powder to the above solution and then treat it with a high-speed dispersion homogenizer at a speed of 5000 r / min for 15 min to obtain a uniform mixed liquid. After vacuum degassing, a wet self-adhesive anti-slip coating material with PVB as binder is obtained.

[0018] The coating material prepared above was applied to a self-made thermoplastic elastomer sample (pure TPE was placed in a mold and hot-pressed in a flat vulcanizing bed for 15 minutes at a molding temperature of 170℃ and a pressure of 20MPa). The sample was then dried at 60℃. The resulting product was tested for dry and wet friction coefficients according to GB / T 3903.37-2008. The measured dry friction coefficient was 0.41, and the wet friction coefficient was 0.58. Example 3

[0019] This embodiment describes the preparation method of an anti-slip coating material with wet self-adhesive function and a floor mat. The steps are as follows: (1) Add 2 parts of dopamine hydrochloride to 100 parts of deionized water and stir to dissolve the dopamine hydrochloride to obtain an aqueous solution of dopamine hydrochloride. Add 40 parts of sodium polyacrylate aqueous solution with a mass fraction of 20% to the aqueous solution of dopamine hydrochloride. After mixing evenly, add tris(hydroxymethyl)aminomethane-hydrochloric acid buffer solution to adjust the pH value to 8.5. Then let it stand at 40°C for 8 hours. During this process, due to the alkaline environment provided by the buffer solution, dopamine hydrochloride is polymerized in situ to generate polydopamine, and a mixed solution containing sodium polyacrylate / polydopamine is obtained. (2) The mixed solution of sodium polyacrylate / polydopamine obtained in step (1) is dried at 80°C, and then pulverized and ground in a ball mill to obtain water-absorbing sodium polyacrylate / polydopamine micro powder with a diameter of 1-3 μm. (3) Add 5 parts of PVB to 100 parts of anhydrous ethanol solvent and stir at high speed for 5 hours at room temperature until completely dissolved to obtain a PVB solution. Add 6 parts of sodium polyacrylate / polydopamine micro powder to the above solution, and then treat it with a high-speed dispersion homogenizer at a speed of 4000 r / min for 15 min to obtain a uniform mixed liquid. After vacuum degassing, a wet self-adhesive anti-slip coating material with PVB as binder is obtained.

[0020] The coating material prepared above was applied to a self-made thermoplastic elastomer sample (pure TPE was placed in a mold and hot-pressed in a flat vulcanizing bed for 15 minutes at a molding temperature of 170℃ and a pressure of 20MPa). The sample was then dried at 60℃. The resulting floor mat was tested for dry and wet friction coefficients according to GB / T 3903.37-2008 standard. The measured dry friction coefficient was 0.47, and the wet friction coefficient was 0.69. Example 4

[0021] This embodiment describes the preparation method of an anti-slip coating material with wet self-adhesive function and a floor mat. The steps are as follows: (1) Add 2.5 parts of dopamine hydrochloride to 100 parts of deionized water and stir to dissolve the dopamine hydrochloride to obtain an aqueous solution of dopamine hydrochloride. Add 35 parts of sodium polyacrylate aqueous solution with a mass fraction of 42% to the aqueous solution of dopamine hydrochloride. After mixing evenly, add tris(hydroxymethyl)aminomethane-hydrochloric acid buffer solution to adjust the pH value to 8.5. Then let it stand at 35°C for 10 hours. During this process, due to the alkaline environment provided by the buffer solution, dopamine hydrochloride is polymerized in situ to generate polydopamine, and a mixed solution containing sodium polyacrylate / polydopamine is obtained. (2) The sodium polyacrylate / polydopamine mixed solution obtained in step (1) is dried at 70°C, and then pulverized and ground in a ball mill to obtain water-absorbing sodium polyacrylate / polydopamine micro powder with a diameter of 1-3 μm. (3) Add 6 parts of PVB to 100 parts of anhydrous ethanol solvent and stir at high speed for 5 hours at room temperature until completely dissolved to obtain a PVB solution. Add 5 parts of sodium polyacrylate / polydopamine micro powder to the above solution, and then treat it with a high-speed dispersion homogenizer at a speed of 4500 r / min for 15 min to obtain a uniform mixed liquid. After vacuum degassing, a wet self-adhesive anti-slip coating material with PVB as binder is obtained.

[0022] The coating material prepared above was applied to a self-made thermoplastic elastomer sample (pure TPE was placed in a mold and hot-pressed in a flat vulcanizing bed for 15 minutes at a molding temperature of 170℃ and a pressure of 20MPa). The sample was then dried at 60℃. The resulting floor mat was tested for dry and wet friction coefficients according to GB / T 3903.37-2008 standard. The measured dry friction coefficient was 0.53, and the wet friction coefficient was 0.75. Comparative Example 1

[0023] This comparative example prepared a TPE floor mat. Pure TPE was placed in a mold and hot-pressed in a flat vulcanizing bed for 15 minutes at a molding temperature of 170℃ and a pressure of 20MPa to obtain a sample for performance testing. The obtained product was tested for dry friction coefficient and wet friction coefficient according to GB / T 3903.37-2008 standard, and the dry friction coefficient was measured to be 0.35 and the wet friction coefficient was 0.24. Comparative Example 2

[0024] This comparative example prepares a coating material and a floor mat. A 50% sodium polyacrylate solution is dried at 100°C, and then pulverized and ground in a ball mill to obtain water-absorbing sodium polyacrylate with a diameter of 1-3 μm.

[0025] Add 3 parts PVB to 100 parts anhydrous ethanol solvent and stir at high speed at room temperature for 3 hours until completely dissolved to obtain a PVB solution. Add 8 parts sodium polyacrylate micro powder to the above solution and then treat it with a high-speed dispersion homogenizer at a speed of 6000 r / min for 15 min to obtain a uniform mixed liquid. After vacuum degassing, a wet self-adhesive anti-slip coating material with PVB as binder is obtained.

[0026] The coating material prepared above was applied to the surface of a self-made thermoplastic elastomer (TPE) sample, which was then placed in a mold and hot-pressed in a flat vulcanizing bed for 15 minutes at a molding temperature of 170℃ and a pressure of 20MPa to obtain the sample. The sample was then dried at 60℃. The obtained product was tested for dry and wet friction coefficients according to GB / T 3903.37-2008 standard. The measured dry friction coefficient was 0.40, and the wet friction coefficient was 0.45.

[0027] As can be seen from the above embodiments and comparative examples, the anti-slip coating material with wet self-adhesion function prepared by the present invention has good dry and wet anti-slip performance, especially outstanding wet anti-slip performance, which is significantly higher than that of TPE body and floor mat coated with sodium polyacrylate, proving that the technical solution of the present invention has achieved good dry and wet anti-slip effect.

[0028] The infrared spectra of pure sodium polyacrylate and the polydopamine / polyacrylic acid prepared in Example 1 are as follows: Figure 1 As shown in the figure, sodium polyacrylate modified with polydopamine has a lower content of 1560 cm⁻¹. -1 A new peak appeared, which is a characteristic peak of the NH group in polydopamine. Meanwhile, the modified sodium polyacrylate showed a peak at 3424 cm⁻¹. -1 The peak area at the modified site increased and shifted to lower frequencies compared to the original state, indicating that the anhydride of sodium polyacrylate has a strong interaction with the amino group in polydopamine.

[0029] Scanning electron microscope (SEM) images of the surface of a pure TPE sheet, the surface of a floor mat coated with the coating material of Comparative Example 1, and the surface of a floor mat coated with the coating material of Example 1 are shown below. Figure 2 As shown in Figures A, B, and C, it can be seen from the figures that the surface of the commercially available pure TPE sheet floor mat and the surface of Comparative Example 1 are relatively smooth, while the surface coated with Example 1 is very rough, consisting of countless particles bonded together, which increases the friction of the floor mat and improves the anti-slip performance of the ground.

[0030] The surface contact angle test results of the anti-slip coating with wet self-adhesive function prepared in Example 1 of this invention are as follows: Figure 3 As shown in the figure, when a water droplet comes into contact with the surface of Example 1, it can be observed that the water droplet spreads out on the coating surface. Water tends to diffuse and be absorbed on the film surface. The water contact angle is small. After 0.8 seconds, the water droplet is almost flat, indicating that the hydrophilic and water-absorbing coating layer has been successfully prepared.

[0031] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing an anti-slip coating material with wet self-adhesive function, characterized in that, Includes the following steps: (1) Add sodium polyacrylate aqueous solution to dopamine hydrochloride aqueous solution and mix well. Then add buffer solution to adjust pH to alkaline, let stand to react, and obtain a mixed solution containing sodium polyacrylate / polydopamine. (2) Dry the mixed solution obtained in step (1), and then pulverize and ball-mill it to obtain sodium polyacrylate / polydopamine micro powder; (3) PVB is added to anhydrous ethanol to dissolve and obtain PVB ethanol solution. Then, the sodium polyacrylate / polydopamine micro powder obtained in step (2) is added to the PVB ethanol solution and homogenized at high speed to obtain a mixed liquid. After vacuum degassing, a non-slip coating material with wet self-adhesive function using PVB as binder is obtained.

2. The method for preparing the anti-slip coating material with wet self-adhesive function according to claim 1, characterized in that: In step (1), the mass fraction of sodium polyacrylate aqueous solution is 20-50%, and the mass fraction of dopamine hydrochloride solution is 0.5-4%.

3. The method for preparing the anti-slip coating material with wet self-adhesive function according to claim 1, characterized in that: In step (1), the volume ratio of sodium polyacrylate aqueous solution to dopamine hydrochloride solution is 3-5:

10.

4. The method for preparing the anti-slip coating material with wet self-adhesive function according to claim 1, characterized in that: In step (1), the buffer solution is a Tris-HCl buffer solution with a pH adjusted to 8.0–9.

0.

5. The method for preparing the anti-slip coating material with wet self-adhesive function according to claim 1, characterized in that: The temperature for the static reaction in step (1) is 30-50°C and the time is 6-12 hours.

6. The method for preparing the anti-slip coating material with wet self-adhesive function according to claim 1, characterized in that: The temperature for drying the mixture in step (2) is 60-100℃; the particle size of the sodium polyacrylate / polydopamine micro powder after grinding is 1-3μm.

7. The method for preparing the anti-slip coating material with wet self-adhesive function according to claim 1, characterized in that: In step (3), the mass fraction of the PVB ethanol solution is 3-8%, and the mass ratio of sodium polyacrylate / polydopamine micro powder to PVB is 1:

1.

8. The method for preparing the anti-slip coating material with wet self-adhesive function according to claim 1, characterized in that: In step (2), the high-speed homogenization speed is 4000-6000 r / min and the time is 6-15 min.

9. A non-slip coating material with wet self-adhesive function prepared by the method according to any one of claims 1-8.

10. The application of the anti-slip coating material with wet self-adhesive function as described in claim 9 in anti-slip floor mats.